Air in the biliary duct as an indicator of Type V Mirizzi syndrome: a case report - Zhang, Jun-Wei; Tian, Feng; Li, Bing-Qi; Wang, Yi-Zhi; Guo, Jun-Chao (Translational Cancer Research; Vol 9, No 2 (February 28, 2020): Translational Cancer Research, 2020)
Mirizzi syndrome, known as extrinsic bile compression syndrome (EBCS), is difficult to diagnose without surgery. To the best of our knowledge, our case shows that air in the biliary duct may indicate Type V Mirizzi syndrome. A 48-year-old Chinese male, complaining of anorexia with weight loss and jaundice, showed decreased bilirubin for two months after being diagnosed with gallbladder stones. Upon re- examination of the CT, evidence of air in the biliary duct was discovered. Type V EBCS was finally diagnosed during surgery. The patient underwent cholecystectomy, cholecystocolic fistula excision, and Roux-en-Y choledochojejunostomy. The postoperative course was uneventful. Mirizzi’s syndrome is a condition which is difficult to diagnose and treat. Air in the biliary duct can be a sign of Type V Mirizzi syndrome, which aids in diagnosis of Type V EBCS before surgery. Cholecystectomy, fistula excision and biliary-enteric anastomosis with Roux-en-Y loop appear to be the most appropriate surgical interventions for the condition.